Microcefalia en Argentina según datos de la Red Nacional de Anomalías Congénitas - Groisman , Boris; Bidondo, María Paz; Liascovich , Rosa (Revista Argentina de Salud Pública, 2016)
Microcephaly in Argentina according to the National Network of Congenital Abnormalities